Rationalization of Health in Java - Ningtyas, Eka (Masyarakat Sejarawan Indonesia, 2020)
This study focuses on the process of rationalizing health in Java with the central issue of dukun bayi or traditional birth attendants from the colonial era to the present day. This research tries to explain how to integrate dukun bayi into modern medicine carried out by the Dutch colonial government and continued by the Indonesian government after independence. In Java since 1851, there has been an official attempt by the government to realize training for dukun bayi by establishing a training center for native midwives. Similar efforts were then continued after Indonesia’s independence through the training conducted by the Department of Health assisted by the local health center. The dukun bayi played a significant role at the beginning of giving birth process but also has a powerful magical element; however, their role in these present days is reduced to being a baby masseur.